2018
DOI: 10.1007/s40145-018-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of transparent nanostructured N-doped TiO2 thin films by combination of sonochemical and CVD methods with visible light photocatalytic activity

Abstract: Pollution of water resources with pesticide compounds has raised serious environmental problems, and for photocatalytic degradation of these pollutants, thin film photocatalysts are preferred to colloidal ones due to the separation problem of colloidal nanoparticles. In this work, nanostructured TiO 2 and N-doped TiO 2 thin films with high transparency were deposited on glass and quartz substrates through sonochemical-chemical vapor deposition (CVD) method. The films prepared on glass and quartz substrates had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 55 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Rasoulnezhad et al . [74] reported the formation of Ti 3+ species in N-doped TiO 2 thin films deposited by chemical vapour deposition. The formation of O v and Ti 3+ could act as electron traps and inhibit the recombination process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rasoulnezhad et al . [74] reported the formation of Ti 3+ species in N-doped TiO 2 thin films deposited by chemical vapour deposition. The formation of O v and Ti 3+ could act as electron traps and inhibit the recombination process.…”
Section: Resultsmentioning
confidence: 99%
“…Figure8aalso shows a red shift displacement of the spin to peak 0.6 eV, indicating the possibility of appearance of Ti 3þ and that, under synthesis conditions, carbon tends to react with oxygen in the TiO 2 lattice leading to the formation of oxygen vacancies (O v ) and the low valence state of Ti 3þ[73]. Rasoulnezhad et al[74] reported the formation of Ti 3þ species in N-doped TiO 2 thin films deposited by chemical vapour deposition. The formation of O v and Ti 3þ could act as electron traps and inhibit the recombination process.…”
mentioning
confidence: 99%
“…Although TiO 2 itself has been proved to be a suitable photocatalyst for oxidation of PCE through PCO, more efforts are needed for further improvement of photocatalytic performance of TiO 2 -based catalysts. Supporting on materials with large surface areas such as glass fiber [15], paint [16], thin-film TiO 2 [17], TiO 2 pellet [18], carbon black or activated carbon [19], carbon nanofibers [20], carbon nanotube [21] is one approach. Another trend is combining or doping TiO 2 with other materials such as Ag [22], Au [23], Sn [24], Pb [25], Ni [26] metal oxides [27] to improve the performance of the photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, there have also been several reports on preparation and photocatalytic activity of the TiO 2 based transparent thin films, such as the S‐doped TiO 2 , Fe‐doped TiO 2 and N‐doped TiO 2 . These films were prepared by the methods of ultrasonic assisted spray pyrolysis technique and combination of sonochemical and CVD processes . These reports concluded that the element‐doped TiO 2 films had highly uniform surfaces and good photocatalytic activities or self‐cleaning potential.…”
Section: Resultsmentioning
confidence: 99%
“…These films were prepared by the methods of ultrasonic assisted spray pyrolysis technique and combination of sonochemical and CVD processes. [39][40][41] These reports concluded that the element-doped TiO 2 films had highly uniform surfaces and good photocatalytic activities or self-cleaning potential. In comparison, the Bi@Bi 4 Ti 3 O 12 /TiO 2 (X-Y) films prepared in this work, showed a strong photocatalytic activity under visible light treatments and displayed a translucent feature.…”
Section: Reusabilitymentioning
confidence: 98%